Earthquake Disaster of Yogyakarta and Central Java, and Disaster Reduction, Indonesia - Sutikno Sutikno (Forum Geografi, 2007)
This paper discussed on earthquake disaster and its reduction of Yogyakarta and Central Java, Indonesia. The study area is located at relatively a short distance from subduction zone of India-Australian and Eurasian plates. Geologically this area is characterized by fault and graben structure, and geomorphologically is composed of block mountain, karsts topography and fluvio-volcanic plain. Aim of this paper is to evaluate the spatial distribution of the damage area, the environmental impacts, and to discuss the risk reduction of earthquake disaster scientifically and practically. In this paper to determine the hazard susceptibility zone and their environmental impact used geologic, geomorphologic, land use map, remote sensing image interpretation, and field observation. Discussion on the earthquake disaster risk reduction based on the hazard susceptibility and the characteristic of the human settlement and facilities. The result of this study shows that: i).the high damage area associate with distribution of the fault structures and the lithology; ii). mass-movement, lowering of groundwater, rising new springs, liquefaction, cracking of rocks and land surface; iii). structural non structural efforts are used for earthquake disaster reduction.